Non-point source pollution of glyphosate and AMPA in a rural basin from the southeast Pampas, Argentina - Okada, Elena (2018)
We measured the occurrence and seasonal variations of glyphosate and its metabolite, aminomethylphosphonic acid (AMPA), in different environmental compartments within the limits of an agricultural basin. This topic is of high relevance since glyphosate is the most applied pesticide in agricultural systems worldwide. We were able to quantify the seasonal variations of glyphosate that result mainly from endo-drift inputs, that is, from direct spraying either onto genetically modified (GM) crops (i.e., soybean and maize) or onto weeds in no-till practices. We found that both glyphosate and AMPA accumulate in soil, but the metabolite accumulates to a greater extent due to its higher persistence. Knowing that glyphosate and AMPA were present in soils (> 93% of detection for both compounds), we aimed to study the dispersion to other environmental compartments (surface water, stream sediments, and groundwater), in order to establish the degree of non-point source pollution. Also, we assessed the relationship between the water-table depth and glyphosate and AMPA levels in groundwater. All of the studied compartments had variable levels of glyphosate and AMPA. The highest frequency of detections was found in the stream sediments samples (glyphosate 95%, AMPA 100%), followed by surface water (glyphosate 28%, AMPA 50%) and then groundwater (glyphosate 24%, AMPA 33%). Despite glyphosate being considered a molecule with low vertical mobility in soils, we found that its detection in groundwater was strongly associated with the month where glyphosate concentration in soil was the highest. However, we did not find a direct relation between groundwater table depth and glyphosate or AMPA detections. This is the first simultaneous study of glyphosate and AMPA seasonal variations in soil, groundwater, surface water, and sediments within a rural basin.